Análisis de los ingresos de los laboratorios clínicos y su incidencia en la recaudación de los impuestos de la provincia de Cotopaxi 2019 - 2021. - Calva Elizalde, Bryan Fernando (2023)
This research is based on the analysis of the income of the clinical laboratories the Cotopaxi province, periods 2019-2021 and its incidence in the collection of taxes, since the collection is the main source of economic income for the Ecuadorian state. The objective of the investigation is to identify the inherent methods, techniques and methodology applied to the object of study and the effects on tax collections for the tax administration. The theoretical bases are based on the analysis of the variables that intervene in the present topic of study, such as: the collection of Income Tax (IR) and Tax on the Exit of Foreign Currency (ISD). The investigation is directed within the quantitative approach, based on the collection of data provided by the Internal Revenue Service (SRI), carrying out a documentary and descriptive investigation, in which the variables that intervene in the collection of taxes were described. Data collection was developed through a database with records of tax collection. The results showed that the impact of COVID-19 in Ecuador significantly reduced tax collection by the Internal Revenue Service (SRI), however, clinical laboratories due to their economic activities of providing health services and in a time of pandemic, was the economic sector that generated the most tax burden for the tax administration, being the period 2020, the date on which the pandemic was officially declared, where the highest level of collection is evident, with a percentage rate of 50% of Income Tax. Income (IR), relative variations of 124% compared to 2019 and -44% compared to 2021, as well as, the Foreign Currency Outflow Tax (ISD) increased in 2020 by 61 %, being its relative variations compared to the periods, 2019-2021, of 360% and -58% respectively. Clinical laboratories constitute an important sector in the economy in Ecuador, which requires a more detailed control of taxpayers, to determine its real impact and tax evasion of some taxpayers.